Bioinspired tetraamino-bisthiourea chiral macrocycles in catalyzing decarboxylative Mannich reactions - Guo, Hao; Ao, Yu-Fei; Wang, De-Xian; Wang, Qi-Qiang (Beilstein Journal of Organic Chemistry, 2022)
A series of tetraamino-bisthiourea chiral macrocycles containing two diarylthiourea and two chiral diamine units were synthesized by a fragment-coupling approach in high yields. Different chiral diamine units, including cyclohexanediamines and diphenylethanediamines were readily incorporated by both homo and hetero [1 + 1] macrocyclic condensation of bisamine and bisisothiocyanate fragments. With the easy synthesis, gram-scale of macrocycle products can be readily obtained. These chiral macrocycles were applied in catalyzing bioinspired decarboxylative Mannich reactions. Only 5 mol % of the optimal macrocycle catalyst efficiently catalyzed the decarboxylative addition of a broad scope of malonic acid half thioesters to isatin-derived ketimines with excellent yields and good enantioselectivity. The rigid macrocyclic framework and the cooperation between the thiourea and tertiary amine sites were found to be crucial for achieving efficient activation and stereocontrol. As shown in control experiments, catalysis with the acyclic analogues having the same structural motifs were non-selective.
Keywords: chiral macrocycles; cooperative asymmetric catalysis; decarboxylative Mannich reactions; supramolecular catalysis; thiourea